Comparative analysis of commercial and “In-House” molecular tests for the detection of intestinal protozoa in stool samples - Giuseppe Di Pietra; Raffaele Gargiulo; Margherita Ortalli; Luciana Petrullo; Ester Oliva; Annibale Raglio; Annachiara Frigo; Ignazio Castagliuolo; Valeria Besutti (Parasites & Vectors)
Abstract Background Pathogenic intestinal protozoa exhibit a global distribution and are significant causes of diarrhea, estimated to affect approximately 3.5 billion individuals annually. These intestinal infections continue to pose formidable diagnostic challenges. Microscopy remains the reference diagnostic method for intestinal protozoa, but is limited in terms of sensitivity, specificity and the ability to differentiate closely related species. Additionally, microscopy requires an experienced microbiologist. Emerging diagnostic methods, such as immunochromatography and enzyme-linked immunosorbent assay (ELISA), are regarded as suitable techniques for rapid screening. Molecular diagnostic technologies, particularly real-time PCR (RT-PCR), are gaining traction in non-endemic areas characterised by low parasitic prevalence owing to their enhanced sensitivity and specificity, although these techniques still face various technical challenges. Methods In this multicentre study involving 18 Italian laboratories, we compared the performance of a commercial RT-PCR test (AusDiagnostics) and an in-house RT-PCR assay against traditional microscopy for identifying infections with Giardia duodenalis, Cryptosporidium spp., Entamoeba histolytica and Dientamoeba fragilis. Results The study analysed 355 stool samples, of which 230 samples were freshly collected and 125 had been stored in preservation media. The data from our analyses show complete agreement between the AusDiagnostics and in-house PCR methods for the detection of G. duodenalis, with both methods demonstrating high sensitivity and specificity, similar to those of conventional microscopy. For Cryptosporidium spp. and D. fragilis detection, both methods showed high specificity but limited sensitivity, likely due to inadequate DNA extraction from the parasite. Molecular assays seem to be critical for the accurate diagnosis of E. histolytica. Overall, PCR results from preserved stool samples were better than those from fresh samples, likely due to better DNA preservation in the former. Conclusions Molecular methods show promise for the diagnosis of intestinal protozoan infections. The molecular assays tested in this investigation performed well for G. duodenalis and Cryptosporidium spp. in fixed faecal specimens, while D. fragilis detection was inconsistent. These results suggest that although PCR techniques are promising in terms of reliable and cost-effective parasite identification, further standardisation of sample collection, storage and DNA extraction procedures is necessary for consistent results. Graphical Abstract